Prototype Software Monitoring Sarana dan Prasarana Perguruan Tinggi - Abdillah, Leon A; Atika, Linda; Kurniawan, Kurniawan; Purwaningtias, Fitri (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
This study aims to facilitate the management system of monitoring infrastructure program of university facilities and infrastructure, through software engineering technology approach as an effort to improve productivity and quality of monitoring process become more efficient and effective. The software in this research is built in a systematic and organized approach to monitoring infrastructure of facilities and infrastructure using appropriate tools and techniques. Through this research, universities are expected to be able to develop the necessary quality measures to support the process of planning and controlling infrastructure infrastructure monitoring. The research was conducted using survey method, development of monitoring management and software. Up to the design stage of this program prototype, research has produced a special picture of the software requirements to be built in the next year. Software development process starting from the analysis phase of system and software requirements, designing data structures up to the architecture stage of the program has produced a list of needs/requirements, the design of program prototype contained in the design of input/output for the monitoring process facilities and infrastructure.